Trust, engagement, information and social licence—insights from New Zealand. (1st February 2019) - Edwards, Peter; Fleming, Aysha; Lacey, Justine; Lester, Libby; Pinkard, Elizabeth; Ruckstuhl, Katharina; Bezuidenhout, Carel; Payn, Tim; Bayne, Karen; Williams, Tracy
Abstract: This research examines trust at the government, industry, community nexus, as mediated by media, and its effect on social licence. We attempted to understand levels and importance of trust in New Zealand's natural resource sectors by examining ways of building, maintaining and assessing public trust in a post-truth society. We surveyed 128 New Zealand public and held a stakeholder forum about perceptions of trust in relation to natural resource sectors. The results provide indications of novel advances around trust and trustworthiness. Honesty was highlighted as the top influencer of trustworthiness and trust, and dishonesty as the top influencer of distrust. In contrast to other literature, we find a nuanced understanding of trust among respondents in relation to the media—respondents distrusted actors cited in media more than the media outlet or platform itself. Further, our findings suggest there is no discernible change in trust levels in the post-truth era, in this context.